Draft Annual Plan (2005-2006) Government of Arunachal Pradesh - Planning Commission (Planning Commission, 2005)
Arunachal Pradesh is known for its ethnic, linguistic, cultural, religious and physiographical diversity The State with a population of only 10.91 lakhs as per 2001 Census inhabiting over an area of 83,743 sq. km. largest amongst NE States, has a very low density of 13 people per sq. km About two third of its population belongs to Scheduled Tribe (64.22%) from 26 major tribes and more than 100 sub-tribes. Arunachal Pradesh is one of the most backward States in the country in the traditional sense of economic parameters. The long isolation and separation, from the mainstream of the country posed formidable problems to the efforts of socio-economic development of the State.
Government of Arunachal Pradesh, Department of Planning